The Representation of a Single Parent Acting as Both Father and Mother in the Film "Memorabilia" - Fajarudin, Muhammad Guntur Satrio; Hariyanto , Didik (Procedia of Social Sciences and Humanities, 2024)
The purpose of this research is to explain the representation of single parents as fathers and mothers in the film "Memorabilia". The method used is a descriptive qualitative method. By using Roland Barthes' theory of semiotic analysis which includes denotation meaning, connotation meaning, and also myth. The results show that there is a representation of single parents as fathers and mothers in the film, including the father's role as protector, the father's role as provider, the father's role as fulfilling nutritional needs, the father's role as a substitute for mother, and the father's role as fulfilling educational needs along with the facilities.